Nanoliposomes and Tocosomes as Multifunctional Nanocarriers for the Encapsulation of Nutraceutical and Dietary Molecules - Ali Zarrabi; Mandana Alipoor Amro Abadi; Sepideh Khorasani; M-Reza Mohammadabadi; Aniseh Jamshidi; Sarabanou Torkaman; Elham Taghavi; M R Mozafari; Babak Rasti (Molecular Diversity Preservation International, 2020)
Nanoscale lipid bilayers, or nanoliposomes, are generally spherical vesicles formed by the dispersion of phospholipid molecules in a water-based medium by energy input. The other nanoscale object discussed in this entry, i.e., tocosome, is a recently introduced bioactive carrier made mainly from tocopheryl phosphates. Due to their bi-compartmental structure, which consists of lipidic and aqueous compartments, these nanocarriers are capable of carrying hydrophilic and hydrophobic material separately or simultaneously. Nanoliposomes and tocosomes are able to provide protection and release of sensitive food-grade bioactive materials in a sustained manner. They are being utilized for the encapsulation of different types of bioactive materials (such as drugs, vaccines, antimicrobials, antioxidants, minerals and preservatives), for the enrichment and fortification of different food and nutraceutical formulations and manufacturing of functional products. However, a number of issues unique to the nutraceutical and food industry must first be resolved before these applications can completely become a reality. Considering the potentials and promises of these colloidal carrier systems, the present article reviews various aspects of nanoliposomes, in comparison with tocosomes, including the ingredients used in their manufacture, formation mechanisms and issues pertaining to their application in the formulation of health promoting dietary supplements and functional food products.